Requirements for managing differentiated classrooms among Jordanian science teachers - Al-Rsa’i, Mohammed S.; Abushwemeh, Zobaida; Krieshan, Eman (Institute of Advanced Engineering and Science, 2025)
Differentiated instruction (DI) is characterized by the fact that it achieves most educational goals and it is role in deepening the values of justice, equity, and a democratic climate in the learning environment. However, this approach requires highly skilled and qualified teachers, especially science teachers, due to the complexity of science learning tasks and environments. The current study aimed to examine the degree to which science teachers in Jordan possess the requirements of differentiated classroom management, and the extent to which they are affected by variables (gender and professional experience). The study sample consisted of 379 science teachers. A differentiated classroom management scale (DCMS) was prepared to achieve the study’s objective, consisting of 38 items with three domains: instruction management, classroom environment management, and managing feelings and emotions in the differentiated classroom. The results of the study showed that the degree to which science teachers in Jordan possess the requirements for differentiated classroom management is moderate. At the same time, there are differences in this degree in favor of the female parameters. However, professional experience did not affect this degree of tenure. The study recommended holding training programs for science teachers in differentiated classroom management and reviewing teacher training programs in Jordan.